Presences of Leonor Fini in the texts of Cristina Peri Rossi - Fariña Busto, María Jesús (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
This article examines the way in which Cristina Peri Rossi introduces references to the painter Leonor Fini in her work. In each case, considerations are offered on the painting evoked and on the text of the writer in which it is included, exposing the similarities and differences between one and the other, as well as examining the significant turns that the literary discourse executes on the pictorial discourse and the functionalities of the latter in relation to the objectives of the former.